Kajian Perkembangan Penelitian Pemasaran Film - Nuryadi Wijiharjono (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
The purpose of this study is to present the most likely conceptual scheme in film marketing research. Based on the study of several leading international journals, many factors are interrelated in film consumption so that the use of quantitative research alone is not sufficient in explaining the phenomenon of film consumption. Factors such as personal involvement with narrative and film characters are worthy of research. Some theories used by journal article writers reviewed in this paper are consumer behavior theory, marketing theory, cognitive theory, communication theory, group dynamics theory, and existentialist phenomenologies. As much. Analysis method on the five articles (quantitative) using regression statistic tool. The data used in the five articles (quantitative) is secondary data. Only on qualitative (phenomenological) approaches that use primary data, directly from the consumer experience.